(untitled) (Bangladesh Journal of Medical Science, 2022)
Aim: This was a descriptive cross sectional study with an aim to find out the occurrences of awareness and use of PPE among the radiographic workers. Methods: The study was conducted among 80 radiographic workers working in 30 different X-ray installations in Dhaka city. Data were collected by direct interviewing of the respondents by using structured questionnaires. Result: Out of all respondents, 93.8%were male and 6.2% were female. Fifty two percent were within the age group 31-40 years. Forty-five percent of all the respondents had higher academic qualification on radiography and eighty-six percent of them were trained in radiography. Ninetynine percent of the workers were aware about using personal protective equipments and Ninetyseven percent were aware about using monitoring devices. However PPE was used by ninety-two percent and radiation monitoring devices by only thirty-six percent. Conclusion: Appropriate protective devices and monitoring devices were not available in most the installations. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 114-119